Risk factors and prognosis of postpericardiotomy syndrome in patients undergoing valve surgery - van Osch, Dirk; Dieleman, Jan M.; Bunge, Jeroen J.; van Dijk, Diederik; Doevendans, Pieter A.; Suyker, Willem J.; Nathoe, Hendrik M.; Bredée, Jaap J.; Buhre, Wolfgang F.; Dieleman, Jan M.; van Dijk, Diederik; van Herwerden, Lex A.; et al. (The Journal of thoracic and cardiovascular surgery, 2017)
The study aim was to investigate the long-term prognosis and risk factors of postpericardiotomy syndrome (PPS). We performed a single-center cohort study in 822 patients undergoing nonemergent valve surgery. Risk factors of PPS were evaluated using multivariable logistic regression analysis. We also compared the incidence of reoperation for tamponade at 1 year between patients with and without PPS. Main secondary outcomes were hospital stay and mortality. Of the 822 patients, 119 (14.5%) developed PPS. A higher body mass index (odds ratio (OR) per point increase, 0.94; 95% confidence interval (CI), 0.89-0.99) was associated with a lower risk of PPS, whereas preoperative treatment for pulmonary disease without corticosteroids (OR, 2.55; 95% CI, 1.25-5.20) was associated with a higher risk of PPS. The incidence of reoperation for tamponade at 1 year in PPS versus no PPS was 20.9% versus 2.5% (OR, 15.49; 95% CI, 7.14-33.58). One-year mortality in PPS versus no PPS was 4.2% versus 5.5% (OR, 0.68; 95% CI, 0.22-2.08). Median hospital stay was 13 days (interquartile range, 9-18 days) versus 11 days (interquartile range, 8-15 days) (P = .001), respectively. Despite longer hospital stays and more short-term reoperations for tamponade, patients with PPS had an excellent 1-year prognosis.